Reoxidation control of refining slag and inclusion modification in TP347H stainless steel - ZHANG Le-chen; BAO Yan-ping; WANG Min; ZHANG Chao-jie (工程科学学报, 2016)
The secondary oxidation caused by compositions of refining slag and Ca treatment on oxide inclusion was studied in TP347H stainless steel by EF+VOD+IC process. In industrial trials, the aluminum is used as the final deoxidation during VOD process. The FeO and SiO2 contents in refining are decreased and the quaternary basicity is higher than 1.3. Then the total oxygen content is below 0.003%. With Ca-Si wire feeding and soft blowing the hard Al2O3 and MgAl2O4 inclusions are transformed to CaO-Al2O3 inclusion. The amount of MgAl2O4 inclusion is reduced and the melting point of inclusion is below 1500℃. This kind of inclu-sion is liquid during steelmaking process and it is easy to coalescence and flotation. And in the following rolling and forging process the inclusions have a little deforming ability with the matrix deformed and prevent the ingot crack.